An Investigation on Surface Roughness and Tool Wear in Turning Operation of Inconel 718 - Gürgen,Selim (2019)
ABSTRACT: This paper investigates the influences of three different input parameters, such as feed rate, insert nose radius, and insert coating methods, in the turning operation of Inconel 718. The coating methods were selected as medium temperature chemical vapor deposition (MT-CVD) and physical vapor deposition (PVD) and in addition to coating methods, the role of various coating materials was discussed since the inserts were coated with multi-layers of TiCN/Al2O3/TiN and single-layer of TiAlN on carbide substrates. The results were discussed in terms of wear behavior of cutting tools and surface quality of the workpiece, which is indicated by surface roughness. A full factorial experimental design was employed in the present work and the results were evaluated using main effects plots. Furthermore, the analysis of variance (ANOVA) method was applied to specify both reactive and non-reactive effects of experimental parameter reactions. The results showed that surface roughness is reduced using low feed rates and large nosed inserts in the operations. Furthermore, TiAlN-coated inserts with PVD method provided better surface finish than with MT-CVD method. It was also found that surface roughness increases as the wear rate of inserts increases.